1994
DOI: 10.2466/pms.1994.78.3c.1323
|View full text |Cite
|
Sign up to set email alerts
|

Factor Analysis and Reliability of the Movement Imagery Questionnaire

Abstract: The purpose of this work was to analyze the factor structure, estimate reliability of the Movement Imagery Questionnaire of Hall and Pongrac, and examine differences between men and women on factor scores. The results for 63 men and 47 women supported the bifactorial structure and reliability of this self-report and its adequacy in comparisons of visual and kinesthetic imagery scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
27
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 5 publications
7
27
0
5
Order By: Relevance
“…Visual imagery was considered "easier", t(13) = 2.51, p = 0.03, in agreement with previous research [2,19]. This suggests that our sample is similar to the neurologically healthy population sampled in motor imagery studies.…”
Section: Imagery Questionnairesupporting
confidence: 90%
“…Visual imagery was considered "easier", t(13) = 2.51, p = 0.03, in agreement with previous research [2,19]. This suggests that our sample is similar to the neurologically healthy population sampled in motor imagery studies.…”
Section: Imagery Questionnairesupporting
confidence: 90%
“…Despite the fact that there was some evidence where males and females presented different imagery generating capabilities, it should be pointed out that different aspects of imagery were examined and only limited differences were discovered (Ozel, Molinaro, & Larue, 2001;Richardson, 1995;Taktek, 2004;Campos, Pérez-Fabello, & Gómez-Juncal, 2004;Williams & Cumming, 2011;Budnik-Przybylska, 2014). For example, females reported higher visual imagery ability than males in some MIQ studies (Atienza, Balaguer, & Garcia-Merita, 1994;Goss, Hall, & Buckolz, 1983). In another study, where the MIQ-R was used, the results also indicated that the model fit females better than males (Monsma, Short, Hall, Gregg, & Sullivan, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence of the MIQ-R's factorial validity is currently lacking, with the majority of existing studies having been conducted on the original MIQ (e.g., Atienza, Balaguer, & Garcia-Merita, 1994). Compared with the MIQ, the MIQ-R has fewer items and the rating scale is reversed.…”
mentioning
confidence: 99%